2022
DOI: 10.3390/agronomy12020269
|View full text |Cite
|
Sign up to set email alerts
|

Current Skills of Students and Their Expected Future Training Needs on Precision Agriculture: Evidence from Euro-Mediterranean Higher Education Institutes

Abstract: This paper set out to explore the precision agriculture (PA)-training needs of students studying in agricultural universities in the Euro-Mediterranean region (Greece, Italy, Portugal and Spain). SPARKLE is a Knowledge Alliance Project, funded by the European Union (EU), and one of its main goals is to narrow the innovation divide between entrepreneurship and the effective application of sustainable PA. During the project, the research conducted in all countries in the Euro-Mediterranean region revealed differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…In total, 67 variables were included and analysed to determine the degree to which these variables were related to each other and to identify cases that had to be excluded. The coefficient value of Cronbach's alpha was found to be equal to 0.93, showing a reliable scale [36][37][38]. It is worth emphasizing that none of the 331 cases were rejected from the analysis.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…In total, 67 variables were included and analysed to determine the degree to which these variables were related to each other and to identify cases that had to be excluded. The coefficient value of Cronbach's alpha was found to be equal to 0.93, showing a reliable scale [36][37][38]. It is worth emphasizing that none of the 331 cases were rejected from the analysis.…”
Section: Methodsmentioning
confidence: 86%
“…Categorical Regression (CATREG) was performed to highlight the possible relationships between the purchase of Chalkidiki reduced-salt green table olives, and a set of other variables. In particular, the CATREG model is a modern regression technique, more holistic and efficient than the most commonly used models [36], and figures relationships between the dependent variable and a set of independent variables [37]. Finally, a normality test was initially performed for hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the lower the 'Technological awareness' 1 is, the slower the automation adoption due to farmers' innovation and imitation is, while the higher the workers' reluctance to accept automation due to related societal threats is. Thus, relevant life-long learning 'Education & training' courses and programmes about agricultural automation/ robotic and their benefits could be essential in rural regions to increase 'Technological awareness' (Alene & Manyong, 2007;Bournaris et al, 2022;Ferrari et al, 2022;Rotz et al, 2019). At the same time, farmers aim to achieve a trade-off between costs and realizable benefits of advanced technologies (Kutter et al, 2011).…”
Section: Current Statementioning
confidence: 99%
“…According to Vázquez-Cano, León Urrutia, Parra-González, and López Meneses (2020) it is necessary to redesign the training matrix in the direction of promoting socially-digital meaningful learning and design the learning environment in an effective, interactive, flexible, and reflective way. Bournaris et al (2022) claim that it is necessary to revise the training program, which integrates improvements in technology and communication, and add precise courses on agriculture for students in all grades. In recent research, it is suggested by Ramalho Ribeiro et al ( 2023) that a tailored interdisciplinary approach, in collaboration with stakeholders, is needed to create a skill set that includes technical skills, digital skills, soft skills, business skills, and market making.…”
Section: Introductionmentioning
confidence: 99%